(untitled) (Revista Contexto & Educação, 2026)
The Science, Technology and Society (CTS) approach to science education enables understanding of the relationships between scientific and technological advances and social contexts. The book “Napoleon’s Buttons: The 17 Molecules That Changed History” presents scientific content in a contextualized way, promoting CTS education and making teaching more meaningful. In view of this, this work proposes a Didactic sequence (DS) with a CTS focus on the indiscriminate use of antibiotics and its consequences for a 10th-grade class, the year in which the curriculum covers the study of organic compounds in a more comprehensive and concrete way. The DS is structured in three pedagogical moments: initial problematization, organization of knowledge, and application of knowledge. This proposal aims to assist teachers in their teaching practice, constituting a valuable teaching tool for chemistry education. In addition, it seeks to contribute to more contextualized and meaningful teaching, stimulating active learning and promoting the development of essential skills and abilities for student autonomy.